Bentonite handbook : lubrication for pipe jacking - Praetorius, Steffen; Schösser, Britta (Ernst & Sohn, 2017)
Pipe jacking is a construction process for the no-dig laying of pipes. Successful pipe jacking demands low skin friction between the ground and the jacked pipe. This is achieved with bentonite lubrication. The bentonite slurry fed into the annular gap fulfils several purposes. It stabilises the annular gap by supporting the surrounding ground and reduces friction contact between ground and jacked pipe. The Bentonite Handbook deals comprehensibly with the relevant aspects of annular gap lubrication: starting with the ground conditions, which are of decisive importance for lubrication, through the rheological properties of the bentonite slurry to the technical components of lubrication technology and lubrication strategy. The use of standardised measuring apparatus is described as well as mixing equipment and the automatic lubrication system. Overview tables with calculations and suggested values for bentonite consumption quantities depending on the prevailing ground conditions and the pipe jacking parameters complete the recommendations.